Asia's greatest wildlife sanctuaries - Lai, Fanny; Olesen, Bjorn (Tokyo: Tuttle Publishing, 2023)
"The Asian continent has the world's highest mountains, hottest deserts and oldest rainforests. And it is the perfect starting point for an exploration of the incredible diversity of wildlife that the world is now in danger of losing due to climate change, population pressures, deforestation and other factors. Take an unforgettable journey to 27 wildlife sanctuaries spread across 14 Asian countries. Here is just a brief taste of what awaits you in these pages: Kanha Tiger Reserve in central India, one of the country's best managed parks and a favourite site to observe the Bengal Tiger. Borneo's Kinabatangan Wildlife Sanctuary, home to some of the highest concentrations of wildlife in Asia, including rich assemblages of large mammals and lowland forest birds. A visit to the jungle-covered islands of the Raja Ampat Archipelago in eastern Indonesia, one of the world's top birdwatching spots, also some of the world's best diving spots. Shiretoko National Park in Hokkaido, Japan, the best sanctuary in Asia to see Brown Bears, with brief and mild summers offering opportunities for whale watching and excellent bird-watching throughout the year. Asia's Greatest Wildlife Sanctuaries is the work of two devoted conservationists who have spent 20 years exploring, documenting and photographing Asia's incredible wildlife. This book is published to raise awareness and funds in support of BirdLife International for their conservation projects in Asia"--
Includes index.
Keywords: Wildlife refuges -- Asia